Educational dimension of judicial self-governance in the exercise of the judicial independence principle: The case of Serbia in the European integration process - Knežević Bojović, Ana; Ćorić, Vesna (Sociološki pregled, 2024)
The rule of law is the cornerstone of democracy and the European Union accession process. Independent judiciary is an important facet of the rule of law, while judicial competence and judicial self-governance are among its elements. One of the dimensions of judicial self-governance is its educational function. By using dogmatic, exegetic and empirical legal methods, the paper examines the extent to which the demands formulated in interim benchmarks for Chapter 23 are aligned with the well-balanced approach to the principle of judicial self-governance and, further, the manner in which such self-governance is implemented in practice within the framework of the process for the adoption of the multiannual work program of the Serbian Judicial Academy. The authors conclude that the plan preparation process represents an adequate platform for duly observing the said concept, while the program itself can contribute to improving the competence of judges and, consequently, strengthening their independence.